2005
DOI: 10.1038/sj.bjc.6602758
|View full text |Cite
|
Sign up to set email alerts
|

Body fatness and physical activity at young ages and the risk of breast cancer in premenopausal women

Abstract: We examined the relationship between body fatness, sports participation and breast cancer risk in 1560 premenopausal cases and 1548 controls, from three related population-based case -control studies in the UK. Half of the women with breast cancer were aged less than 36 years at diagnosis. Women who perceived themselves as plump at age 10 years had a relative risk of 0.83 (95% confidence interval 0.69 -0.99, P ¼ 0.03) as compared with those who perceived themselves as thin. Self-reported obesity compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 20 publications
(26 reference statements)
2
37
0
Order By: Relevance
“…This is mainly attributed to hormonal profiles that are higher in circulating levels of steroid hormones caused by increased adipose tissue conversion that may enhance tumor growth (3). In contrast, studies among premenopausal women have generally found modest inverse associations between body weight and breast cancer incidence (4,5). This may be due to lower levels of bioavailable estrogens that are a result of anovulatory cycles, which can occur more frequently with obesity (6).…”
Section: Introductionmentioning
confidence: 63%
“…This is mainly attributed to hormonal profiles that are higher in circulating levels of steroid hormones caused by increased adipose tissue conversion that may enhance tumor growth (3). In contrast, studies among premenopausal women have generally found modest inverse associations between body weight and breast cancer incidence (4,5). This may be due to lower levels of bioavailable estrogens that are a result of anovulatory cycles, which can occur more frequently with obesity (6).…”
Section: Introductionmentioning
confidence: 63%
“…This association of shape and age implies a shift in fat toward the upper body with age and, within the upper body, to a preferential distribution around the waist rather than the arm and bust. In premenopausal women, overweight and obesity are associated with a lower risk of breast cancer (27,28); however, in postmenopausal women, overweight increases the risk (29). The redistribution of weight to the upper body with increasing age, which increases the bust, may contribute to this changing association between BMI and the risk of cancer.…”
Section: Discussionmentioning
confidence: 98%
“…In Geneva, prevalence of obesity has increased among adolescents and young females (Morabia and Costanza, 2005), but, in contrast to post-menopausal women, it appears to be protective against breast cancer in young women (Bouchardy et al, 1990;Magnusson et al, 2005;Michels et al, 2006). Smoking still seems to be increasing among women in Geneva and, compared with older women, young women begin smoking cigarettes at a much earlier age and are heavier smokers (Costanza et al, 2006).…”
Section: Discussionmentioning
confidence: 99%